Manajemen Kegiatan Intra Dan Ekstrakurikuler Dalam Pembentukan Karakter Peserta Didik pada Madrasah Aliyah Negeri - Abd Wahid; Ridwan Ridwan; Laziman Laziman; Rufaidah Mama (JITU Jurnal Ilmiah Tarbiyah Umat, 2025)
The development of intra- and extracurricular activities in madrasas plays a strategic role in shaping students' character. This study aims to examine the management of intra- and extracurricular activities and the realization of character formation, while identifying supporting and inhibiting factors at Madrasah Aliyah Negeri 1 Polewali Mandar. The approach used was qualitative through field studies using observation, interviews, and documentation techniques. The results of the study indicate that management activities are carried out according to management functions, including planning, organizing, implementing, and supervising. Planning is carried out through coordination meetings and teacher training, organizing includes the division of tasks and the appointment of supervisors, while implementation focuses on academic, extracurricular, and religious training. Supervision is carried out directly by the madrasah principal. The main findings indicate that intra- and extracurricular activities are effective in strengthening students' character formation. Supporting factors include the leadership of the madrasah principal, openness, and teacher professionalism, while inhibiting factors are limited civil servant educators, science laboratory facilities, computer facilities, and the availability of open books.